ANALISIS LAMA PEMAKAIAN KONTRASEPSI DEPO MEDROKSI PROGESTERON ASESTAT DENGAN GANGGUAN MENSTRUASI - vittria meilinda (HUMAN CARE JOURNAL, 2021)
Depo Medroxy Progesterone Acetate (DMPA) is a contraceptive in the form of injections given every three months containing the hormone progestin. This contraceptive is given by injection in the buttocks/arm area. The purpose of this study was to determine the analysis of the duration of the use of Depo Medroxy Progesterone Acetate injectable contraception with and menstrual disorders in the Bungo area in 2020. The research design used was a descriptive analytical method with a cross sectional approach. The population includes all mothers who use DMPA injection family planning with a sample of 77 respondents. The sampling technique was simple random sampling. The data used are secondary data and primary data obtained from data obtained from the Bungo City area. Data analysis using square test. The results showed that the use of DMPA injectable contraception was under 1 year and 84.6% used DMPA injectable contraception for more than 1 year and 6.5% under 1 year and 88.3% for more than 1 year using DMPA injectable contraception experienced menstrual disorders. Based on the results of the study, it was concluded that there was an effect of the duration of the use of DMPA injection family planning with menstrual disorders. So it is recommended to be able to often provide counseling about family planning counseling, especially DMPA injections because it is in great demand by family planning acceptors